2020
DOI: 10.1155/2020/4562418
|View full text |Cite
|
Sign up to set email alerts
|

Pickling Behaviour of 2205 Duplex Stainless Steel Hot‐Rolled Strips in Sulfuric Acid Electrolytes

Abstract: Pickling behaviour of the oxide layer on hot-rolled 2205 duplex stainless steel (DSS) was studied in H2SO4 solutions with electrolytic workstation. The pickling rate at 75 ºC increases slightly with the H2SO4 concentration from 100 to 250 g L -1 , but increases markedly as the concentration is higher than 250 g L -1 . The solution temperature greatly accelerates the pickling rate. Fe 3+ ion is an effective oxidant, which shows stronger inhibitive effect. The rotating disk electrode was used to simulate the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In contrast, Figure 4(b) showed that the metal surface pre-treated with sulfuric acid appears smoother, with only a little debris found on the surface. A similar finding had been reported [23], where static pickling produced a smoother surface than dynamic pickling.…”
Section: Surface Morphologysupporting
confidence: 88%
“…In contrast, Figure 4(b) showed that the metal surface pre-treated with sulfuric acid appears smoother, with only a little debris found on the surface. A similar finding had been reported [23], where static pickling produced a smoother surface than dynamic pickling.…”
Section: Surface Morphologysupporting
confidence: 88%
“…Kalasin, NN, et al [25] investigated the dissolution rate of scales on hot-rolled steel strips made from continuous cast slabs and the time required for complete dissolution through pickling tests. To simulate the motion of an actual strip, Peng, JG, et al [26] employed a rotating disk electrode to study the pickling performance of iron oxide on the surface of 2205 duplex stainless steel hot-rolled strips in a sulfuric acid electrolyte.…”
Section: Introductionmentioning
confidence: 99%